Review of the genus Merarius Fairmaire (Coleoptera: Anthribidae), with description of two new species from China - Trýzna, Miloš; Baňař, Petr (Zootaxa, 2021)
The genus Merarius (Anthribidae: Anthribinae: Tropiderini) from the Oriental and Palaearctic regions is reviewed. Two new species, M. alexandrae Trýzna & Baňař sp. nov. and M. korinae Trýzna & Baňař sp. nov., from China are described. Male and female genitalia of M. korinae are studied and illustrated. A key to the now five known species of the genus, colour photographs and new data on distributions are provided.